2011
DOI: 10.1159/000334641
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Systemic Delivery of Substrates for Intermediate Metabolism during Citrate Anticoagulation of Continuous Renal Replacement Therapy

Abstract: Background: There are limited data on systemic delivery of metabolic substrates during citrate anticoagulation. The direct citrate measurements are usually not available. Methods: Patients on 2.2% acid-citrate-dextrose (ACD, n = 41) were compared to a control group on unfractionated heparin (n = 17). All were treated on 1.9-m2 polysulfone filters. Samples were taken from the central venous catheter, ports pre- and post-filter and from effluent. Results: The gain of citrate in CVVH (n = 18) was not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…In the absence of high lactate delivery, a substantial gain or loss of energy would not be expected from the replacement fluids because of the small difference in glucose concentrations between these fluids and blood. The only previous demonstration of energy gain with the use of citrate for anticoagulation to our knowledge is that from Balik et al (10,11), who reported that when an acid-citrate-dextrose solution is used with high lactate replacement fluids, CRRT can provide #1300 kcal/d. Our results are more relevant to the most recently published Improving Global Outcomes Acute Kidney Injury Work Group acute kidney injury guidelines (14), which recommend lactate-free replacement fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of high lactate delivery, a substantial gain or loss of energy would not be expected from the replacement fluids because of the small difference in glucose concentrations between these fluids and blood. The only previous demonstration of energy gain with the use of citrate for anticoagulation to our knowledge is that from Balik et al (10,11), who reported that when an acid-citrate-dextrose solution is used with high lactate replacement fluids, CRRT can provide #1300 kcal/d. Our results are more relevant to the most recently published Improving Global Outcomes Acute Kidney Injury Work Group acute kidney injury guidelines (14), which recommend lactate-free replacement fluids.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who require nutritional support, there is a strong relation between the amount of feeding administered and both hyperglycemia and insulin requirements (8). Continuous renal replacement therapy (CRRT) is now used universally in hemodynamically unstable individuals with acute and chronic kidney impairment, and it has been recognized as a potential source for macronutrient losses as well as macronutrient uptake, depending on the composition of the fluids used (9)(10)(11)(12). However, to our knowledge, the possibility for net macronutrient uptake has not been mentioned in published guidelines from nephrology and nutrition societies (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Besides a mildly higher lactate load in CVVHDF there were no clinically important differences between the modalities confirming similar impact of diffusive and convective membrane transfer on small molecules with a sieving coefficient about 1.0 [7,18]. Higher gain of lactate in CVVHDF could be explained by the countercurrent effect of dialysis fluid plus significant postdilution [3,7]. …”
Section: Discussionmentioning
confidence: 92%
“…The aim of calorimetry was to compare the impact of citrate and lactate on oxygen consumption (VO 2 ) and CO 2 production, RQ and energy expenditure (EE) [13]. The bioenergetic gains of citrate and lactate [3,7] as well as loss of glucose were quantified at 9-hour intervals. All patients received a standard nutritional regimen of 3 g/kg/day of glucose, 1.5 g/kg/day of amino acids, and 1 g/kg/day of fat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation